2012
DOI: 10.1080/21507716.2011.640654
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Decision Making and Adults with Intellectual Disability: A Descriptive Survey

Abstract: Background: Intellectual disability occurs in approximately 7 to 8 million Americans. The literature demonstrates that this population experiences communication

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Although previous experiences with decision-making did not influence informed consent in this paper, other studies have suggested that people with intellectual disability who are accustomed to independent decision-making are more able to make informed medical decisions. [59, 60] Individuals with intellectual disability who live independently were more likely to make independent healthcare decisions, compared to those who lived with parents or carers. [58]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous experiences with decision-making did not influence informed consent in this paper, other studies have suggested that people with intellectual disability who are accustomed to independent decision-making are more able to make informed medical decisions. [59, 60] Individuals with intellectual disability who live independently were more likely to make independent healthcare decisions, compared to those who lived with parents or carers. [58]…”
Section: Resultsmentioning
confidence: 99%
“…Although previous experiences with decision-making did not influence informed consent in this paper, other studies have suggested that people with intellectual disability who are accustomed to independent decision-making are more able to make informed medical decisions. [59,60] Individuals with intellectual disability who live independently were more likely to make independent healthcare decisions, compared to those who lived with parents or carers. [58] 5.2 Insufficient education for people with intellectual disability about their healthcare rights Another subtheme identified in five of the 23 included studies [49,52,58,65,67] was that people with intellectual disability were not adequately informed that they have health choices or that they can refuse treatment.…”
Section: Previous Experience Of People With Intellectual Disability W...mentioning
confidence: 99%
“…[ 3 15 16 24 25 26 27 ] Prevalence of ID gradually drops in adults from the age of 20 years in both rural and urban population. However, the literature indicates some studies of covariates of ID[ 28 29 30 31 32 ] These studies have been mostly based on clinical and not necessarily covariates from a population perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Available research in the field has not shown favorable results for individuals with ID when their healthcare decisions are solely determined by the appointed decision makers, support staff, and healthcare professionals (O'Dell, Leafman, Nehrenz, & Bustillos, ). The authors suggest that the structured views and perspectives of the organization's key stakeholders may help the management understand the reality of organizational life that can support them in long‐term decision making.…”
Section: Introductionmentioning
confidence: 99%